The Role of Configural Processing in Face Classification by Race: An ERP Study - Lv, Jing; Yan, Tianyi; Tao, Luyang; Zhao, Lun (Frontiers in Human Neuroscience, 2015)
The current study investigated the time course of the other-race classification advantage (ORCA) in the subordinate classification of normally configured faces and distorted faces by race. Slightly distorting the face configuration delayed even more the categorization of own-race faces having no conspicuous effect on other race faces. The N170 was not sensitive to configural distortions and faces’ races. The P3 was enhanced for other-race than own-race faces and reduced by configural manipulation only for own-race faces. We suggest that the source of ORCA is the configural analysis applied by default while processing own-race faces.